The Voice of the Authorized Heritage Discourse: A Critical Analysis of Signs at Ancient Monuments in Skåne, Southern Sweden - Anders Högberg (Current Swedish Archaeology, 2012)
The study presents an investigation of a regional authorized heritage discourse, represented by the County Administrative Board on signs set up at an- cient monuments and sites in the province of Skåne in southern Sweden. The starting point is a critical analysis of layout, texts and illustrations to ascertain the narratives conveyed by the signs. The results show that slightly less than half of the studied signs work well according to the criteria set up for the study. The result also demonstrates that more than half of the studied signs do not work well according to these cri- teria. Those that work well give detailed information about the ancient monument or site. The signs that do not work well give inadequate information and risk excluding a majority of the people who read them. The latter signs confirm what so many other discourse analyses have shown, that the authorized heritage dis- course to a large extent still privileges the perspectives of a white, middle-class male. The former signs, that is, those that are judged to work well in terms of the criteria applied in this study, show that the authorized heritage discourse does not only offer something that privileges the perspectives of that white, middle class male, but also has the ability to offer narratives with other perspectives.